ANALISA KEPUASAN KONSUMEN JASA PARKIR AMBON PLAZA DI KOTA AMBON - Alvian - Sapulette (Politeknik Negeri Semarang, 2014)
The purpose of this study was to determine the dimensions of service quality, is it has a positive effect on user satisfaction parking services, also in order to identify and analyze dimensions of the service quality, are those significantly influence the Ambon Plaza parking service users.The sampling technique used was purposive sampling, with the following requirements: 1. Age 17 years and above; 2. Able to communicate; 3. In a conscious state; 4. Already using parking services to and over 3 times; 5. Willing to be interviewed, with a sample of 100 respondents. Methods used in data collection, were : questionnaires, interview and observations. The technique analysis used was the Multiple Regression Analysis.The analysis shows, that the dimensions of service quality: tangibles, realiability, responsiveness, assurance and empathy simultaneously positive and significant impact on user satisfaction parking service. On the other hands partially known, that the dimensions who has a significant impact on user satisfaction parking service, was the responsiveness dimension.